Global hotspots and trends in pre-metastatic niche research: a bibliometric analysis(2005-2024) - Mengqi Cheng; Mengqi Cheng; Qianhui Sun; Qianhui Sun; Hua Duan; Hua Duan; Cihui Chen; Cihui Chen (Frontiers in Immunology)
BackgroundThe pre-metastatic niche (PMN) represents the microenvironment established in target organs before primary tumor metastasis, playing a crucial role in organ-specific metastasis. Understanding and preventing PMN formation holds promise for enhancing immunotherapy efficacy and reducing cancer-related mortality. Despite the significance of this field, a comprehensive bibliometric analysis is lacking. This study aims to identify global research trends and hotspots in PMN through a systematic bibliometric evaluation, providing a foundation for future advancements in this field.MethodsPublications related to PMN research from 2005 to 2024 were retrieved from the Web of Science Core Collection database. Bibliometric analyses and visualizations were conducted using VOSviewer, CiteSpace, Microsoft Excel, ArcGIS, Scimago Graphica, and Microsoft Charticulator.ResultsThe study included 1,303 publications authored by 7,955 researchers from 1,627 institutions across 62 countries, with articles published in 400 journals. China and the United States emerged as central contributors to global PMN research. China has led in publication volume and institutional representation, while the United States has produced the most high-quality papers and impactful authors. Cancers published the most PMN-related papers, while Cancer Research had the most citations and co-citations. Professor David Lyden of Cornell University, USA, was identified as the most influential scholar in the field. Analysis of references and keywords suggests future research will focus on metastatic organotropism, extracellular vesicles, innate immunocytes (e.g., macrophages and neutrophils), and immunotherapy.ConclusionThis bibliometric study represents the first comprehensive analysis of global scientific output in PMN research over the past two decades. By summarizing the current status and identifying trends in the field, this study provides valuable insights and a reference point for researchers aiming to prevent and treat tumor metastasis effectively.